background image

4. ABOUT INFINITE CASE

36

3. Finite boolean lattices

We can assume

B

=

P

B

for a set

B

, card

B

=

n

. Then

f

pFCD

(

A

;

B

)

⇔ ∀

X

A

, Y

B

: (

h

f

i

X

6

Y

f

1

Y

6

X

)

⇔ ∀

X

A

, Y

B

: (

i

Y

:

i

∈ h

f

i

X

f

1

Y

6

X

).

Having values of

f

1

{

i

}

we can restore all

h

f

1

i

Y

. [need this paragraph?]

Let

T

i

=

n

X

A

i

∈h

f

i

X

o

.

Let now

T

i

P

A

be ideals. Can we restore

h

f

i

? Yes, because we know

i

∈ h

f

i

X

for every

X

A

.

So, it is equivalent to:

X

A

, Y

B

: (

i

Y

:

X

T

i

f

1

Y

6

X

)

.

(1)

Lemma

2214

.

The formula (

1

is equivalent to:

X

A

, i

B

: (

X

T

i

f

1

{

i

} 6

X

)

.

(2)

Proof.

(

1

)

(

2

). Just take

Y

=

{

i

}

.

(

2

)

(

1

). Let (

2

holds.

Let also

X

A

, Y

B

.

Then

h

f

1

i

Y

6

X

S

i

Y

h

f

1

i{

i

} 6

X

⇔ ∃

i

Y

:

h

f

1

i{

i

} 6

X

⇔ ∃

i

Y

:

X

T

i

.

Further transforming:

i

B

:

T

i

=

h

f

1

i{

i

}

.

So

f

1

{

i

}

are arbitary elements of

B

and

T

i

are corresponding arbitrary

principal ideals.

In other words,

pFCD

(

A

;

B

)

=

A

Π

. . .

Π

A

(card

B

times). Thus

pFCD

(

A

;

B

) is

a boolean lattice.

4. About infinite case

Let

A

be a complete boolean lattice,

B

be an atomistic boolean lattice.

f

pFCD

(

A

;

B

)

⇔ ∀

X

A

, Y

B

: (

h

f

i

X

6

Y

f

1

Y

6

X

)

⇔ ∀

X

A

, Y

B

: (

i

atoms

Y

:

i

atoms

h

f

i

X

f

1

Y

6

X

).

Let

T

i

=

n

X

A

i

atoms

h

f

i

X

o

.

T

i

is an ideal: Really: That it’s an upper set is obvious.

Let

P

Q

n

X

A

i

atoms

h

f

i

X

o

. Then

i

atoms

h

f

i

(

P

Q

) = atoms

h

f

i

P

atoms

h

f

i

Q

;

i

∈ h

f

i

P

i

h

f

i

Q

.

Let now

T

i

P

A

be ideals. Can we restore

h

f

i

? Yes, because we know

i

atoms

h

f

i

X

for every

X

A

and

B

is atomistic.

So, it is equivalent to:

X

A

, Y

B

: (

i

atoms

Y

:

X

T

i

f

1

Y

6

X

)

.

(3)

Lemma

2215

.

The formula (

3

is equivalent to:

X

A

, i

atoms

B

: (

X

T

i

⇔ h

f

1

i

i

6

X

)

.

(4)

Proof.

(

3

)

(

4

). Let (

3

holds. Take

Y

=

i

. Then atoms

Y

=

{

i

}

and thus

X

T

i

⇔ ∃

i

atoms

Y

:

X

T

i

f

1

Y

6

X

f

1

i

6

X

.

(

4

)

(

3

). Let (

2

holds.

Let also

X

A

,

Y

B

.

Then

f

1

Y

6

X

h

f

1

i

d

atoms

Y

6

X

d

i

atoms

Y

f

1

i

6

X

⇔ ∃

i

atoms

Y

:

f

1

i

6

X

⇔ ∃

i

atoms

Y

:

X

T

i

.

Further equivalently transforming:

i

atoms

B

:

T

i

=

f

1

i

.

So

f

1

i

are arbitary elements of

B

and

T

i

are corresponding arbitrary prin-

cipal ideals.